Systematic Literature Review: Peer Conformity to Smoking Behavior in Adolescent Boys - Afra Nuha Irwan; Neviyarni S (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
Conformity pressure in peer groups is one of the factors that most influence the emergence of smoking behavior in adolescent boys. The classic findings of Solomon Asch's experiments provide the basis that individuals can adjust their opinions and actions when under the pressure of majority norms. In line with this, various public health studies and social network research have highlighted the mechanisms of influence and selection as the main explanation for why smoking behavior can spread in adolescent groups. This literature review examines in detail 10 major empirical studies related to the relationship between conformity and smoking behavior in adolescents, along with additional analysis from 25 other scientific sources. The results of the study showed that normative group pressure, social status in the school network, closeness to close friends, and social relationship patterns affect adolescents' chances of starting smoking. Its interaction with other environmental factors suggests that conformity does not work alone, but is interrelated to the process of social selection and group dynamics. These findings hint at the importance of social network-based interventions and strengthening anti-smoking norms as prevention strategies.